The Effectiveness of Educational Videos on Knowledge, Perception, and Anxiety About COVID-19 Vaccination - Nughroho, Ariyanto; Fadlilah, Siti; Muflih, Muflih (Universitas Negeri Semarang cooperate with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Background: The vaccination program is the main focus of handling COVID-19 at this time. Insufficient knowledge, poor perceptions, and high levels of anxiety can affect the success of the COVID-19 vaccination program. Health education is an option for overcoming these problems. Aims: This study was to find out the effect of health education through videos on knowledge, perception and anxiety in the community in the selected area In Indonesia. Method: Research used a quasi-experimental with a pretest-posttest control group. The sample consisted of the control and intervention groups, with 221 samples each taken by accidental sampling. This research was conducted in July-September 2021. The intervention provided was a health education video about COVID-19 vaccination for 13.27 minutes. The instrument consists of a self-reported questionnaire. Bivariate data test used Wilcoxon Signed Ranks Test and Mann Whitney. Result: The control group showed decreasing knowledge score of 1.0, an increased perception score of 0.4, and an anxiety score of 0.1. The group showed increased knowledge and perception scores (6.0 and 4.0), while the Anxiety score also decreased by 13.8. The pretest and posttest tests of the control group showed knowledge (p=0.0060), perception (p=0.202), and anxiety (p=0.659). The pretest and posttest of the intervention group for all variables showed p<0.001. The posttest difference test for all variables between the control and intervention groups was p<0.001. Conclusions: Health education through video effectively increases knowledge and perception and reduces anxiety about COVID-19 vaccination